Islamic Work Ethics and Employee Social Responsibility of Service Sector in Saudi Arabia. Mediating Role of Organizational Identification - Almasradi , Rajeh Bati (Journal of Ecohumanism, 2024)
This paper aims to establish how Islamic Work Ethics relates to Employee Social Responsibility Saudi Arabia’s service sector, focusing on the mediating effect of Organizational Identification. Islamic Work Ethics, encompassing fairness, honesty, and responsibility, is crucial for individual and organizational success through commitment and accountability. The study hypothesizes that Islamic Work Ethics positively affects Employee Social Responsibility, actions that support the social objectives of companies and society. Quantitative data were obtained via cross-sectional survey questionnaires from 349 professionals in the Saudi service sector. The results indicate a significant correlation between Islamic Work Ethics (independent variable) and Employee Social Responsibility (dependent variable), suggesting that employees adhering to Islamic Work Ethics are more likely to exhibit socially responsible behaviors. Additionally, Organizational Identification, which measures employees’ psychological attachment to their organization, plays a key mediating role in this relationship. Employees with strong Organizational Identification are more likely to align their self-promotion with organizational goals, including social responsibility. This research highlights the importance of integrating Islamic ethical values to enhance social responsibility in organizations and provides valuable insights into management practices in regions where Islamic culture is predominant.